[Connie and her daughter] - Orchid Contreras::::::photographer::: (2005)
Description supplied by photographer: 'Mi cuñada Connie y su hija sentadas en el patio de mi casa en San Juan Nuevo y la está alimentando con Caldo de Pollo. Mi cuñada labora fabricando ropa. Tomé esta foto el primer dia que llegue a San Juan Nuevo. Solamente nos vemos una vez al año.' - 'My sister in law Connie is feeding her daughter chicken soup at my familys house in San Juan Nuevo. My sister in law makes clothing for a living. I took this photo the first day I arrived in San Juan Nuevo. We get to see each other only once a year.'